AKSI BERSIH PANTAI TERHADAP PENGURANGAN SAMPAH DAN MENJAGA KEBERLANJUTAN LINGKUNGAN DI KAWASAN PANTAI MARINA SEMARANG: Beach Clean-up Action Towords Waste Reduction and Maintaining Environmental Sustainability in The Marina Beach Area, Semarang - Assauri, Supian; Khussaniah, Mina; Janah, Rodhotul; Latifah, Nur; Abiyi, Royan Majid; Hikmah, Ahmad Aulia Ulil; ., Mutma'inah (Yayasan Al-Amin Qalbu, 2024)
Waste pollution in the Marina Beach area of Semarang has reached a critical stage, threatening ecosystem sustainability and reducing the beach's tourist attraction. The background of this issue prompted a community service initiative aimed at reducing waste volume in the coastal area and increasing public awareness about environmental preservation. The implementation method employed a descriptive-observational approach, including direct beach condition observations, beach clean-up actions, and tree planting as a symbolic environmental restoration effort. The service results demonstrated a significant reduction in waste volume and increased participant awareness of environmental issues. Through provided education, the activity successfully encouraged a shift in community mindset regarding waste management and the importance of environmental conservation. Tree planting contributed to ecosystem damage mitigation efforts, with the hope of providing long-term benefits for coastal environmental sustainability